2020
DOI: 10.1364/ol.378606
|View full text |Cite
|
Sign up to set email alerts
|

Convex silica microlens arrays via femtosecond laser writing

Abstract: We report fabrication of silica convex microlens arrays with controlled shape, size, and curvature by femtosecond laser direct writing. A backside etching in dye solution was utilized for laser machining high-fidelity control of material removal and real-time surface cleaning from ablation debris. Thermal annealing was applied to reduce surface roughness to 3 nm (rms). The good optical performance of the arrays was confirmed by focusing and imaging tests. Complex 3D micro-optical elements over a footprint of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…Backside wet etching + thermal annealing Fused silica Hua et al [12] Ablation of microholes + wet etching Silicon Pan et al [13] Ablation of microholes + wet etching Fused silica, sapphire Zhang et al [14] Modification of photosensitive glass Foturan glass Lin et al [15] + thermal treatment, wet etching, annealing Ablation (pressure & resoldification) PDMS Yong et al [16] Ablation (pressure & resoldification) Chalcohalide glass Kadan et al [17] Two-photon polymerization Photoresist Wu et al [18] Two-photon polymerization Photoresist He et al [19] Laser ablation + CO laser polishing Fused silica Choi et al [20] Laser ablation + CO 2 laser polishing Soda-lime glass Delgado et al [21] While lens arrays are often fabricated via thermal reflow processes [22][23][24], several alternative methods such as ink-jetting [25], reactive ion etching [26] or hot embossing [27] have been demonstrated. Recently, femtosecond laser-based lens array fabrication techniques have been developed which are summarized in Table 1.…”
Section: Technology Materials Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Backside wet etching + thermal annealing Fused silica Hua et al [12] Ablation of microholes + wet etching Silicon Pan et al [13] Ablation of microholes + wet etching Fused silica, sapphire Zhang et al [14] Modification of photosensitive glass Foturan glass Lin et al [15] + thermal treatment, wet etching, annealing Ablation (pressure & resoldification) PDMS Yong et al [16] Ablation (pressure & resoldification) Chalcohalide glass Kadan et al [17] Two-photon polymerization Photoresist Wu et al [18] Two-photon polymerization Photoresist He et al [19] Laser ablation + CO laser polishing Fused silica Choi et al [20] Laser ablation + CO 2 laser polishing Soda-lime glass Delgado et al [21] While lens arrays are often fabricated via thermal reflow processes [22][23][24], several alternative methods such as ink-jetting [25], reactive ion etching [26] or hot embossing [27] have been demonstrated. Recently, femtosecond laser-based lens array fabrication techniques have been developed which are summarized in Table 1.…”
Section: Technology Materials Referencementioning
confidence: 99%
“…Recently, femtosecond laser-based lens array fabrication techniques have been developed which are summarized in Table 1. Hua et al [12] demonstrated the usage of the femtosecond laser in a backside wet etching process for geometry generation, which is followed by thermal annealing to smoothen the surface to fabricate microlens arrays in silica. Pan et al [13] and Zhang et al [14] showed the microlens array fabrication by femtosecond laser production of microholes and a subsequent wet etching step forming the lens geometry on silicon as well as silica and sapphire, respectively.…”
Section: Technology Materials Referencementioning
confidence: 99%
“…The micro/nanostructures of such SQ materials may be fabricated using semiconductor fabrication technologies. These SQ microstructures may be utilised in macro-lens arrays 11 15 . SQ plates with structures smaller than visible wavelengths demonstrate unique optical functions in waveguide circuits 16 , photonic crystals 17 , 18 , and metalenses 19 .…”
Section: Introductionmentioning
confidence: 99%
“…These SQ microstructures may be utilised in macro-lens arrays. [11][12][13][14][15] SQ plates with structures that are smaller than visible wavelengths demonstrate unique optical functions in waveguide circuits, 16 photonic crystals, 17,18 and metalenses. 19 Plates with concave/convex nanometre-scale patterns can be fabricated from SQ using electron beam (e-beam) lithography and have been used as templating moulds, which demonstrate high mechanical repeatability and light transparency in ultraviolet nanoimprint lithography for the mass production of semiconductor and optical devices.…”
Section: Introductionmentioning
confidence: 99%